POTENTIATED PROCESSING OF NEGATIVE FEEDBACK IN DEPRESSION IS ATTENUATED BY ANHEDONIA. Issue 4 (23rd January 2015) - Mueller, Erik M.; Pechtel, Pia; Cohen, Andrew L.; Douglas, Samuel R.; Pizzagalli, Diego A.
Abstract : Background: Although cognitive theories of depression have postulated enhanced processing of negatively valenced information, previous EEG studies have shown both increased and reduced sensitivity for negative performance feedback in MDD. To reconcile these paradoxical findings, it has been speculated that sensitivity for negative feedback is potentiated in moderate MDD, but reduced in highly anhedonic subjects. The goal of this study was to test this hypothesis by analyzing the feedback‐related negativity (FRN), frontomedial theta power (FMT), and source‐localized anterior midcingulate cortex (aMCC) activity after negative feedback. Methods: Fourteen unmedicated participants with Major Depressive Disorder (MDD) and 15 control participants performed a reinforcement learning task while 128‐channel Electroencephalogram (EEG) was recorded. FRN, FMT, and LORETA source‐localized aMCC activity after negative and positive feedback were compared between groups. Results: The MDD group showed higher FRN amplitudes and aMCC activation to negative feedback than controls. Moreover, aMCC activation to negative feedback was inversely related to self‐reported anhedonia. In contrast, self‐reported anxiety correlated with feedback‐evoked frontomedial theta (FMT) within the depression group. Conclusions: The present findings suggest that, among depressed and anxious individuals, enhanced processing of negative feedback occurs relatively early in the information processing stream. These results extend prior work and indicate that although moderate depression is associated with elevated sensitivity for negative feedback, high levels of anhedonia may attenuate this effect.